ENGELLİLERDE SPORTİF BECERİ VE KOORDİNASYON EĞİTİM PROGRAMLARI - (:unkn) unknown (My University, 2015)
Sportif beceri ve koordinasyon (SBK) eğitimleri, engelli rehabilitasyonunu eğlenceli ve sürdürülebilir hale getirmek için tasarlanmıştır. Hekim muayenesini takiben programa kabul edilen engellilere fizyoterapist değerlendirmesi ve farklı sportif beceri/yeteneklerine yönelik değerlendirme testleri uygulanmaktadır. Kişiye özel egzersiz programı belirlendikten sonra ortalama 12 hafta ve haftada 2-3 seanslık SBK eğitimi uygulanmaktadır. Dönem sonunda, başlangıçta yapılan muayene ve testler tekrar edilerek programın başarısı değerlendirilmektedir. Program, özellikle omurilik yaralanmalı ve serebral palsili çocukların fiziksel performanslarında belirgin iyileşmeler, brakial pleksus yaralanması gibi sürekli egzersiz programı ihtiyacı duyulan çocuklarda egzersize katılımda artışlar sağlamıştır. Fiziksel katkılarının yanında engelli ve ailesinin ruh durumlarında da ölçülebilir değişiklikler kaydedilmektedir

Sport skills and coordination (SSC) education was designed to make disabled rehabilitation fun and sustainable. Handicapped children have been accepted to the program by physician examination. In addition to this, they went through physiotherapist evaluation and several assessment tests for different sport skills/talents. Based on these evaluations, a personalized exercise program is set for each child and 2 to 3 sessions of SSC training per week for approximately 12 weeks is applied. At the end of the training period, initially made tests and evaluations at the program acceptance are re-performed in order to assess the program success. Program has been provided significant improvements in the performance of the children with spinal cord injuries and cerebral palsy; and a substantive increase in the program participation was observed for the children who are constantly needed exercise program (i.e. children with brachial plexus). Measurable positive changes in the mood of handicapped children and their families are recorded alongside the physical contribution of the program.
SPORT SKILLS AND COORDINATION TRAINING PROGRAMS FOR HANDICAPPED CHILDREN
Keywords: Tarih